2015
DOI: 10.1177/0003489415570933
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Controlled Release on TGF-β1 Treated Vocal Fold Fibroblasts

Abstract: Objective Corticosteroids may be beneficial in treating vocal fold scarring. Current drug delivery methods do not permit controlled corticosteroid release. Here we investigate the effects of poly-lactic-co-glycolic acid (PLGA) microparticles loaded with the corticosteroid dexamethasone in reducing collagen synthesis and inflammation in vocal fold fibroblasts treated with and without TGF-β1. Study Design Experimental, in vitro study. Methods PLGA microparticles of differing molecular weight and terminating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
10
0
2
Order By: Relevance
“…A previous study revealed decreased collagen deposition in an injured rabbit VF model after dexamethasone injection 9 . Significant depression of collagen gene expression was noted 9 . In a clinical study, Wang et al identified 22 patients that developed VF fibrosis following microlaryngeal excisional surgeries 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed decreased collagen deposition in an injured rabbit VF model after dexamethasone injection 9 . Significant depression of collagen gene expression was noted 9 . In a clinical study, Wang et al identified 22 patients that developed VF fibrosis following microlaryngeal excisional surgeries 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed that phlorotannins significantly suppressed the expression level of COL I and cell migration in TGFβ-stimulated hVFFs without exhibiting cytotoxicity, showing an inhibitory efficiency similar to treatment with 0.2 μg/ml MMC. A previous study reported that 1% w/v dexamethasone-loaded poly-lactic-coglycolic acid microparticles were less potent than phlorotannins isolated from E. cava (Kosinski, Pothen, Panitch, & Sivasankar, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Our results revealed that phlorotannins significantly suppressed the expression level of COL I and cell migration in TGF‐β‐stimulated hVFFs without exhibiting cytotoxicity, showing an inhibitory efficiency similar to treatment with 0.2 μg/ml MMC. A previous study reported that 1% w/v dexamethasone‐loaded poly‐lactic‐ co ‐glycolic acid microparticles were less potent than phlorotannins isolated from E. cava (Kosinski, Pothen, Panitch, & Sivasankar, 2015). Additionally, hepatocyte growth factor and interleukin‐6 have demonstrated antifibrotic activity at concentrations lower than phlorotannins by inhibiting the expression level of fibrotic markers, but their activity was less efficient (Vyas, Ishikawa, Duflo, Chen, & Thibeault, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kosinski et al antifibrotic effects of dexamethasone were tested in immortalized human VF fibroblasts by quantitative polymerase chain reaction (qPCR) for mRNA of collagen [ 19 ]. Comparable methods were used by Suehiro et al in a study with rat VF fibroblasts [ 20 ].…”
Section: Discussionmentioning
confidence: 99%